On the Q–S Chaos Synchronization of Fractional-Order Discrete-Time Systems: General Method and Examples. (10th September 2018) - Ouannas, Adel; Khennaoui, Amina-Aicha; Grassi, Giuseppe; Bendoukha, Samir
Abstract : In this paper, we propose two control strategies for theQ –S synchronization of fractional-order discrete-time chaotic systems. Assuming that the dimension of the response systemm is higher than that of the drive systemn, the first control scheme achievesn -dimensional synchronization whereas the second deals with them -dimensional case. The stability of the proposed schemes is established by means of the linearization method. Numerical results are presented to confirm the findings of the study.